The Law Is (Not) for Kids A Legal Rights Guide for Canadian Children and Teens - Lecic, Ned (Athabasca University Press, 2019)
In this practical guide to the law for young people of Canada, Ned Lecic and Marvin Zuker provide an all-encompassing manual meant to empower and educate children and youth and those that serve them. The authors address questions about how rights and laws affect the lives of young people at home, at school, at work, and in their relationships as they draw attention to the many ways in which a person's life can intersect with the law. Deliberately refraining from taking a moral approach, the authors instead advocate for the rights of children and provide examples of how young people can get their legal rights enforced. In addition to being critical information for youth about citizenship, The Law is (Not) for Kids is a valuable resource for teachers, counsellors, lawyers, and all those who support youth in their encounters with the law.